Entrepreneurship and urban farming: A study on determinants of business management - Muhammad Hasan; Muhammad Dinar; Nur Arisah; Marhawati Marhawati; Andi Asti Handayani (Journal of Enterprise and Development (JED), 2023)
Purpose — This research was conducted to find out how entrepreneurship education, entrepreneurial experience, and entrepreneurial motivation influence the management of farming in urban areas.Method — This research was conducted using a quantitative approach with associative methods and employing multiple linear regression data analysis techniques. The research population consisted of members of the Citra women's farmer group, totaling 20 people located at BTN Citra Tello Permai, Tello Baru Village, Panakkukang District, Makassar City.Result — The results of the research indicate that the entrepreneurial education variable has a positive and significant effect on the management of urban farming businesses, the entrepreneurial experience variable also has a positive and significant effect on the management of urban farming businesses, while the entrepreneurial motivation variable, partially, shows no positive and significant effect on the management of urban farming businesses.Contribution — This research makes a valuable academic contribution by addressing a population gap, as prior studies primarily centered on MSMEs, with limited exploration of the crucial urban agricultural sector.